On the Legal Basis of the Protection of Entities Engaged in Operational-Search Activity - USPANOV, Zholdybay (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article reveals the main constitutional guarantees of entities engaged in operational-search activity, and their relationship with the civilian population. Institute of constitutional rights and freedoms of citizens in legal form reflects a fundamental change in the status of the individual in the legal community and its relations with the state. Contemporary Kazakh society started construction of a new, independent, legal, democratic state. The leading form of law is not ideological, but value consciousness. The need for an axiological understanding of the problems of law is rooted in the fundamental questions of human existence. Values are closely connected with the concept of the meaning of human life. The law for a long time was dominated by the idea of legal positivism. The Republic of Kazakhstan is now facing the task to adjust the national legal system, for the universal values to be demanded by civil society. Today, the Constitution enshrines the rights and freedoms for the entire population and ensures the safety of the actors performing the operational-search activity.